Pengaruh Pemberian Pupuk NPK Phonska Terhadap Pertumbuhan Dan Produksi Tanaman Kacang Panjang (Vigna sinensis L) varietas Aura Jaguar - Supandji Supandji; Edy Kustiani; Agus Purwanto (Kadiri University, 2021)
This study aimed to determine the effect of Phonska NPK fertilizer on the growth and production of asparagus beans (Vigna sinensis L). A hypothesis is that applying Phonska NPK fertilizer at a 200 kg/ha dose is suspected to affect the growth and yield of long beans (Vigna sinensis L). This research was carried out in rice fields in Gempolan Village, Gurah District, Kediri Regency, East Java Province, from November 2020 to February 2021. The study was carried out using a simple Randomized Block Design (RAK) experimental method, repeated three times with one factor. Phonska NPK fertilizer dosage treatment (P) consists of 7 levels P0 = Without Phonska NPK fertilizer. P1 = Phonska NPK administration with a dose of 50 kg hectare-. P2 = Phonska NPK administration with a dose of 100 kg hectares-1 =. P3 = Phonska NPK administration at a dose of 150 kg ha-1. P4 = Phonska NPK administration at a dose of 200 kg ha-1. P5 = Phonska NPK administration at a dose of 250 kg ha-1. P6 = Phonska NPK administration at a dose of 300 kg ha-1 . The results showed that the application of Phonska NPK fertilizer significantly affected the observations of plant height, number of leaves, number of flowers per plant, number of pods per plant, weight of consumption pods per plant, and weight of consumption pods per hectare. The highest yield was achieved at a 200 kg NPK Phonska/ha fertilizer dose for a plant height of 237.75 cm. The number of leaves was 111.50 pieces. Phonska NPK fertilizer treatment at a 200 kg/ha dose resulted in 20,750 flowers, 112,500 pods per plant, 616,250 grams per plant weight, and 27,385 tons per hectare production per hectare. Penelitian ini bertujuan untuk mengetahui pengaruh pemupukan Phonska NPK terhadap pertumbuhan dan produksi tanaman kacang panjang (Vigna sinensis L). Penelitian dilakukan di lahan persawahan milik petani di Desa Gempolan, Kecamatan Gurah, Kabupaten Kediri, Provinsi Jawa Timur. November 2020 hingga Februari 2021. Penelitian ini menggunakan metode eksperimen Rancangan Acak Kelompok (RAK), satu faktor dan diulang sebanyak 3 kali. Perlakuan dosis pupuk Phonska NPK (P) meliputi 7 taraf, P0= kontrol, P1= pemberian NPK Phonska dengan dosis 50 kg hektar-1 , P2= pemberian NPK Phonska dengan dosis 100 kg hektar-1 , P3= pemberian NPK Phonska dengan dosis 150 kg hektar-1 , P4= pemberian NPK Phonska dengan dosis 200 kg hektar-1 , P5= pemberian NPK Phonska dengan dosis 250 kg hektar-1 , P6= pemberian NPK Phonska dengan dosis 300 kg hektar-1 . Hasil penelitian menunjukkan bahwa pemupukan NPK Phonska memberikan pengaruh sangat nyata terhadap nilai pengamatan tinggi tanaman, jumlah daun, jumlah bunga, dan jumlah polong per tanaman. Berat polong yang dapat dimakan per tanaman dan berat polong yang dapat dimakan per hektar. Hasil terbaik ditunjukkan oleh dosis pupuk 200 kg/ha untuk tinggi tanaman sebesar 237,75 cm, jumlah daun sebanyak 111,50 buah. Perlakuan dosis pupuk NPK Phonska dengan dosis 200 kg/ha menghasilkan jumlah bunga sebesar 20.75 buah, jumlah polong per tanaman sebesar 112,500 buah, berat polong sebesar 616,25 gram per tanaman dan produksi tiap hektar sebesar 27,38 ton/ha.